Membangun Kemandirian Ekonomi: Pelatihan Manajemen Usaha untuk Pekerja Migran Indonesia di Desa Gabusbanaran, Tembelang, Jombang - Chusnul Rofiah; Rita Mutiarni; Deni Widyo Prasetyo (Institut Nalanda, 2025)
The Business Management Training for Indonesian Migrant Workers (PMI) in Gabusbanaran Village, Tembelang, Jombang, was designed to improve the entrepreneurial capacity of PMI in utilizing remittance funds productively. This program integrates theoretical and practical approaches through business planning, financial management, and marketing strategies. The implementation method includes a survey of participant needs, provision of theoretical materials, practical simulations, and post-training assistance to ensure the sustainability of implementation. The evaluation results showed a significant increase in participant competence, with an average increase in ability of 24.87%, based on a comparison of pretest and posttest scores. Participants showed progress in understanding the concept of entrepreneurship, preparing business plans, and using digital technology for marketing. However, this training faced obstacles such as low technological literacy, limited business capital, and lack of participant confidence. To overcome these obstacles, ongoing assistance, simplification of training materials, and strengthening access to technology are needed. In addition to providing a positive impact on individual participants, this program contributes to village economic development through the formation of local entrepreneur communities. With a systematic and sustainability-oriented approach, this training can be a strategic model in similar community empowerment programs in other areas